Electrochemical behavior of dissimilar welded joints between ASTM A615 and AISI 304 with and without buttering using Inconel 182 - Ramírez Soto, Juan Carlos Isidro; Pérez-Quiroz, José Trinidad; Salgado-López, Juan Manuel; Pérez-López, Tezozomoc; Rendón-Belmonte, Mariela; Álvarez-Alfaro, Erick; Martínez-Madrid, Miguel (Revista ALCONPAT, 2019)
In this study, the corrosion performance of dissimilar welded joints between ASTM A615 and AISI 304 stainless steel with and without buttering using Inconel 182 was evaluated. In both cases, the filler metal was ER-309L and the base metals were prepared with a 45° single bevel. One half of the specimens were welded with “buttering” using Inconel 182. The electrochemical results showed that despite welding defects, the welded specimens formed a passive layer in alkaline environments. The specimens welded with buttering exhibited the best corrosion resistance and mechanical properties.